Documents concerning Central Europe from the Hospital's Rhodian Archives
1 online resource.
Keywords: "Documents Concerning Central Europe from the Hospital's Rhodian Archives, 1314-1428 brings together over 400 texts concerning the Hospitallers during the fourteenth and fifteenth centuries. These texts are crucial sources for understanding the history of the Hospitallers between 1314 and 1428. Whilst some Hospitaller charters and letters have been published elsewhere, few scholarly editions contain enough sources to permit close analysis of the language and content of these documents. Moreover, most previous editions focus on certain geographical areas, such as Cyprus, Rhodes, and the Aegean Islands. In contrast, this book is the first of its kind to focus on central Europe. It brings together 461 texts dated between 1314 to 1428, and two from 1461. This book will appeal to scholars and students of medieval history and the history of central Europe, as well as those interested in the legal structures and personal networks within the Order of St. John"--